Environmentally Related Diseases and the Possibility of Valuation of Their Social Costs - Ilona Hajok; Ewa Marchwińska; Grzegorz Dziubanek; Bernadeta Kuraszewska; Agata Piekut (The Scientific World Journal)
The risks of the morbidity of the asbestos-related lung cancer was estimated in the general population of Poles as the result of increased exposure to asbestos fibers during the removal of asbestos-cement products and the possibility of the valuation of the social costs related to this risk. The prediction of the new incidences was made using linear regression model. The forecast shows that to the end of 2030 about 3,500 new cases of lung cancer can be expected as a result of occupational exposure to asbestos in the past which makes together with paraoccupational exposure about 14.000 new cases. The forecast shows the increasing number of asbestos-related lung cancer in Poland and indicates the priority areas where preventive action should be implemented.